REFORMING THE ACCOUNTING SYSTEM IN THE CONDITIONS OF UKRAINE’S EUROPEAN INTEGRATION - Kladnytska, Tetiana; Borkovska, Valentyna; Kovalova, Tetiana (Social Development: Economic and Legal Issues, 2025)
In Ukraine, a large-scale process of modernization of the accounting system and financial reporting in the public sector is underway, which takes into account the requirements of international standards, in particular with an orientation towards European integration obligations. The relevance of the study is due to the need to adapt the national accounting system to European standards and principles, including the organization of tax accounting and reporting. The study summarizes the problems of adapting the national accounting system to the conditions of European integration. Martial law, as an emergency, significantly affects the economy of the country and the enterprise, which is reflected in accounting. Recognition of extraordinary events has a significant impact on the reflection of performance results and financial condition in financial statements, in particular on the adjustment of events after the reporting period, assessment of the going concern principle, and presentation of financial statements that adjust reforms within the framework of European integration. The purpose of the study is to determine the ability of the national accounting system to provide reliable information on the financial and economic situation of the enterprise in the context of the European integration processes of Ukraine. In addition, the purpose is to analyze the possibility of the accounting methodology of institutional sectors of the economy to ensure the formation of the necessary information during martial law. Attention is also focused on the need to continue reforms in the field of accounting. The results of the study contain a systematization of the main areas of reform and the results of the modernization of the public finance management system in Ukraine, with a focus on increasing transparency and adaptation to European integration requirements. Key problems and challenges that require improvement and systematization of the main strategic documents in this direction are identified. The conclusions indicate that the implementation of the Strategy for Modernizing Accounting and Financial Reporting in the Public Sector will contribute to the adaptation of legislation to international accounting and reporting standards, increasing the reliability and transparency of financial reporting, which is a necessary condition for ensuring effective management of public finances in Ukraine.